Wear-resistant flexible high polymer material and preparation method thereof

By combining wear-resistant components and antioxidants with polypropylene base material and preparing through a twin-screw extrusion mechanism, the problem of insufficient wear resistance and low-temperature toughness of polypropylene composite materials is solved, and wear-resistant flexible polymer materials with high mechanical strength, good wear resistance and low-temperature impact resistance are achieved.

CN119875248APending Publication Date: 2025-04-25BUFFALO TECH (NINGBO) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510046886.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing polypropylene composite materials lack wear resistance and low temperature toughness during use, which limits their application range.

Method used

采用一种耐磨柔性高分子材料,通过将无规共聚聚丙烯、抗冲共聚聚丙烯、乙烯-辛烯共聚物等与耐磨组分、抗氧剂、成核剂等组合,并通过双螺杆挤出机制备,形成具有独特柔性缓冲结构的材料。

Benefits of technology

The material still maintains good impact resistance at minus 30 degrees Celsius, has extremely strong rigidity and flexibility, high mechanical strength, wear resistance and insulation properties, avoiding the problems of high brittleness and poor notch impact strength under low temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005238728480000111
    Figure BDA0005238728480000111
  • Figure BDA0005238728480000121
    Figure BDA0005238728480000121
Patent Text Reader

Abstract

The invention discloses a wear-resistant flexible high polymer material and a preparation method thereof, and belongs to the technical field of high polymer materials. Comprising the following raw materials in parts by weight: 300 to 350 parts of polypropylene random copolymer, 250 to 280 parts of impact-resistant polypropylene copolymer, 210 to 240 parts of ethylene-octylene copolymer, 45 to 55 parts of wear-resistant component, 21 to 35 parts of antioxidant, 10 to 12 parts of nucleating agent, 9 to 10 parts of maleic anhydride graft, 4 to 5 parts of aminotriazole, 14 to 15 parts of basic magnesium sulfate whisker, 13 to 15 parts of ultraviolet light absorber and 7 to 8 parts of lubricant. The wear-resistant component is polystyrene-CeO2 composite microspheres modified by a PDMS-based coupling agent, the whole obtained product has extremely high rigidity and flexibility and very good mechanical strength, local stress can be released to other parts of the product, and the product does not crack; good impact resistance is still kept at the temperature of 30 DEG C below zero.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a wear-resistant flexible polymer material and a preparation method thereof. Background Art

[0002] Polypropylene (PP) is a good thermoplastic resin with the properties of being colorless, non-toxic, lightweight, having good thermal stability and good electrical insulation. It is widely used in the automotive industry, daily necessities, construction and other fields. However, polypropylene has the problem of poor wear resistance and scratch resistance. In particular, poor wear resistance will cause the gloss of acrylic materials to continue to decrease during use, which greatly limits the application of acrylic acid.

[0003] At present, the method for improving the wear resistance of polypropylene is generally to add inorganic wear-resistant agents or organic scratch-resistant agents to the polypropylene mixture. Inorganic wear-resistant agents include materials such as graphene oxide and molybdenum disulfide. On the one hand, due to their own dark color, they are easy to affect the final aesthetics of the product. On the other hand, due to their small particle size, they are easy to agglomerate, resulting in a decrease in the mechanical properties of the composite material. Organic scratch-resistant agents are mostly amide scratch-resistant agents, but amide scratch-resistant agents will make the surface of the material sticky and cause the problem of atomization value, and there are carbon-carbon double bonds that are prone to aging and degradation. In addition, under low temperature conditions, the movement of PP molecular chains is limited, the crystallinity is high, and there are problems such as large molding shrinkage, high brittleness, and poor notched impact strength, which limit its comprehensive performance in low temperature conditions. Therefore, providing a polypropylene composite material with high wear resistance and good low-temperature toughness is a technical problem that needs to be solved at present. Summary of the invention

[0004] The purpose of the present invention is to provide a wear-resistant flexible polymer material and a preparation method thereof, so as to solve the problems of poor wear resistance and low-temperature toughness of existing polypropylene composite materials.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A wear-resistant flexible polymer material comprises the following raw materials in parts by weight: 300-350 parts of random copolymer polypropylene, 250-280 parts of impact copolymer polypropylene, 210-240 parts of ethylene-octene copolymer, 45-55 parts of wear-resistant components, 21-35 parts of antioxidants, 10-12 parts of nucleating agents, 9-10 parts of maleic anhydride grafts, 4-5 parts of aminotriazole, 14-15 parts of basic magnesium sulfate whiskers, 13-15 parts of ultraviolet absorbers, and 7-8 parts of lubricants.

[0007] Furthermore, the wear-resistant component is a PDMS-based coupling agent modified polystyrene-CeO2 composite microsphere.

[0008] Furthermore, the preparation process of the wear-resistant component is as follows:

[0009] The polystyrene-CeO2 composite microspheres are ultrasonically dispersed in an ethanol solution, a PDMS-based coupling agent and a zinc chloride ethanol solution are added, and the mixture is stirred and mixed at 60-80°C for 12 hours, and then filtered. The filter cake is washed with deionized water and dried to obtain a wear-resistant component.

[0010] PDMS-based coupling agent is hydrolyzed to produce silanol, which is then grafted with polystyrene-CeO2 composite microspheres through a coupling reaction, and through the coordination relationship between Schiff base and zinc ions, a wear-resistant component with surface-loaded zinc ions is obtained.

[0011] Furthermore, the dosage ratio of the polystyrene-CeO2 composite microspheres, the ethanol solution, the PDMS-based coupling agent and the zinc chloride ethanol solution is 10g: 100-150mL: 0.5-1g: 5-10mL, and the mass fraction of zinc chloride in the zinc chloride ethanol solution is 10-12%.

[0012] Furthermore, the PDMS-based coupling agent is prepared by an ammonia-aldehyde condensation reaction of triethoxysilylbutyraldehyde and NH2-PDMS-NH2.

[0013] Furthermore, the preparation process of the PDMS-based coupling agent is as follows:

[0014] Dissolve triethoxysilyl butyraldehyde in toluene, add NH2-PDMS-NH2, stir for 3-5 minutes, then drop glacial acetic acid, heat to 120°C and react for 24 hours, then remove toluene by rotary evaporation to obtain a PDMS-based coupling agent;

[0015] In the above process, the usage ratio of triethoxysilylbutyraldehyde, toluene, NH2-PDMS-NH2 and glacial acetic acid is 2mmol:30mL:1mmol:0.15-0.6mL.

[0016] Furthermore, NH2-PDMS-NH2 is amino-polydimethylsiloxane-amino with a molecular weight of 700-5000.

[0017] Furthermore, the preparation process of the polystyrene-CeO2 composite microspheres is as follows:

[0018] Step a, adding distilled water, styrene, divinylbenzene and methacrylic acid into a reaction kettle, stirring evenly under nitrogen protection, heating to 75° C., adding potassium persulfate solution, keeping the temperature for reaction for 6 hours, and cooling to room temperature to obtain a polystyrene microsphere emulsion;

[0019] Step b, adding the polystyrene microsphere emulsion into distilled water, adding hexamethylenetetramine and cerium nitrate hexahydrate after ultrasonic dispersion for 10 minutes, reacting at 75° C. for 2 hours under stirring conditions, then centrifuging, washing the precipitate with anhydrous ethanol and drying to obtain polystyrene-CeO2 composite microspheres.

[0020] Furthermore, in step a, the dosage ratio of distilled water, styrene, divinylbenzene, methacrylic acid and potassium persulfate is 60 mL: 10 mL: 0.5 mL: 0.75 mL: 0.125 g, and the mass fraction of the potassium persulfate solution is 2%.

[0021] Furthermore, in step b, the usage ratio of the polystyrene microsphere emulsion, distilled water, hexamethylenetetramine and cerium nitrate hexahydrate is 4 mL: 200 mL: 2.44 g: 1.51 g.

[0022] Firstly, polystyrene microspheres were prepared by soap-free emulsion polymerization, and polystyrene-CeO2 composite microspheres with a "soft core and hard shell" structure were prepared by liquid phase process using cerium nitrate and hexamethylenetetramine as raw materials and polystyrene microspheres as the core.

[0023] Furthermore, the aminotriazole is at least one of 3-amino-1,2,4-triazole, 3,5-diamino-1,2,4-triazole, 5-amino-1H-1,2,4-triazole-3-carboxylic acid, 4-aminotriazole, 5-amino-1H-1,2,4-triazole-3-ethylcarboxylate and 5-amino-1H-1,2,4-triazole-3-carboxylic acid.

[0024] Furthermore, the maleic anhydride grafted product is maleic anhydride grafted polypropylene.

[0025] Furthermore, the random copolymer polypropylene is PP-R material of Korea Hyosung, brand R200P.

[0026] Furthermore, the impact-resistant copolymer polypropylene is polypropylene with a PP grade of J340 produced by PetroChina Panjin Ethylene Co., Ltd.

[0027] Furthermore, the ethylene-octene copolymer is ethylene-octene copolymer of brand 8842 produced by The Dow Chemical Company of the United States.

[0028] Furthermore, the antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 18-20:13-15.

[0029] Furthermore, the nucleating agent is HPN-20E.

[0030] Furthermore, the ultraviolet absorber is UV-531.

[0031] Furthermore, the lubricant is ethylene bisstearamide.

[0032] The preparation method of the above-mentioned wear-resistant flexible polymer material comprises the following steps:

[0033] Random copolymer polypropylene, impact copolymer polypropylene, maleic anhydride grafted product and aminotriazole are added to an internal mixer, and blended at a speed of 50 rpm and 100° C. for 15 minutes to obtain a pretreated material. The pretreated material, ethylene-octene copolymer, wear-resistant component, antioxidant, nucleating agent, ultraviolet absorber and lubricant are added to a twin-screw extruder through a main feeding port, and basic magnesium sulfate whiskers are added through a side feeding port, followed by melt extrusion to obtain a wear-resistant and flexible polymer material.

[0034] Furthermore, the screw temperature of the twin-screw extruder is 180-230° C., preferably 190-220° C., and the rotation speed is 200-600 rpm, preferably 220-400 rpm.

[0035] Beneficial effects of the present invention:

[0036] 1. The present invention provides a wear-resistant flexible polymer material, which is mainly made of copolymerized polypropylene, and is introduced with wear-resistant components, aminotriazole and other substances, and is integrated with antioxidants, high-toughness polyolefins and other structural polymer materials. It has a unique flexible buffer structure, can absorb impact force and restore itself to its original state, the integration of polymer chains is stable and firm, the product as a whole has extremely strong rigidity and flexibility, and very good mechanical strength, and can release local stress to other parts of the product, and the product will not crack; this stable molecular structure also enables the product to quickly recover its appearance after being stressed, and maintains the appearance of the product itself; the product still maintains good impact resistance at minus 30 degrees Celsius, and its wear resistance, insulation and cold resistance are all good.

[0037] 2. The present invention introduces a wear-resistant component into a polypropylene base material. The wear-resistant component has a soft-core and hard-shell structure. The polymer core in the wear-resistant component makes it inherently flexible. At the same time, due to the coating of CeO2 nanoparticles on the surface, it has considerable surface hardness. When it is introduced into the polypropylene matrix, when subjected to external force, it dissipates energy through large deformation and cavitation through the interface layer with excellent compatibility, thereby achieving excellent toughening effect. In addition, its surface contains a PDMS-based coupling agent, which has low surface tension and good mobility. During the processing, the PDMS-based coupling agent will migrate to the surface of the material with the wear-resistant component, so that the wear-resistant component is mainly distributed on the surface of the workpiece. Based on the lubricating effect of silicone and the wear resistance of CeO2, the wear resistance of the workpiece is significantly improved.

[0038] 3. In the process of preparing the wear-resistant flexible polymer material, the random copolymer polypropylene, the impact copolymer polypropylene, the maleic anhydride graft and the aminotriazole are preferentially reacted at 100°C for a period of time, so as to make the maleic anhydride group in the maleic anhydride graft react with the amino group on the aminotriazole, graft the aminotriazole onto the side chain of the maleic anhydride graft, and then blend with polypropylene to obtain a polypropylene matrix carrying triazole groups, and then blend and extrude with the wear-resistant component to form a "Schiff base-Zn" inside the composite material. 2+ -triazole" metal coordination bond. The formation of the metal coordination bond can improve the strength and toughness of the material. The reason is that the metal coordination bond, as a sacrificial bond, can bear part of the force when the material is stressed. It breaks and dissipates a lot of energy before the covalent bond of the polymer main chain breaks, which can ultimately enhance and toughen the material itself. DETAILED DESCRIPTION

[0039] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0040] It should be understood that in the various embodiments of the present application, the size of the serial number of each process does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the implementation regulations of this application.

[0041] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0042] The technical solution of the present application is illustrated below through specific embodiments and comparative examples.

[0043] The maleic anhydride grafted modified polypropylene in this application is model 200A, and the weight average molecular weight is 13×10 4g / mol, the maleic anhydride grafting rate is 0.6-1wt%, and the manufacturer is Nengzhiguang New Materials Technology Co., Ltd.; the random copolymer polypropylene is the PP-R material of Korea Hyosung, with the brand R200P; the impact copolymer polypropylene is produced by China Petroleum Panjin Ethylene Co., Ltd., with the brand J340; the ethylene-octene copolymer is the 8842 brand ethylene-octene copolymer of the Dow Chemical Company of the United States, the nucleating agent is HPN-20E, the ultraviolet absorber is UV-531, and the lubricant is ethylene bisstearamide.

[0044] Preparation Example 1

[0045] The preparation process of polystyrene-CeO2 composite microspheres is as follows:

[0046] Step a, adding 60 mL of distilled water, 10 mL of styrene, 0.5 mL of divinylbenzene and 0.75 mL of methacrylic acid into a reaction kettle, stirring evenly under nitrogen protection, heating to 75° C., adding a potassium persulfate solution containing 0.125 g of potassium persulfate, the mass fraction of the potassium persulfate solution being 2%, keeping the temperature for reaction for 6 hours, and cooling to room temperature to obtain a polystyrene microsphere emulsion;

[0047] Step b: add 4 mL of polystyrene microsphere emulsion into 200 mL of distilled water, add 2.44 g of hexamethylenetetramine and 1.51 g of cerium nitrate hexahydrate under ultrasonic dispersion for 10 min, react at 75 ° C for 2 h under stirring conditions, then centrifuge, wash the precipitate with anhydrous ethanol and dry it to obtain polystyrene-CeO2 composite microspheres.

[0048] Preparation Example 2

[0049] The preparation process of the wear-resistant component is as follows:

[0050] 10 g of the polystyrene-CeO2 composite microspheres prepared in Preparation Example 1 were ultrasonically dispersed in 100 mL of ethanol solution, 0.5 g of a PDMS-based coupling agent and 5 mL of a zinc chloride ethanol solution were added, wherein the mass fraction of zinc chloride in the zinc chloride ethanol solution was 10%, and the mixture was stirred and mixed at 60° C. for 12 h, then filtered, and the filter cake was washed with deionized water and dried to obtain a wear-resistant component.

[0051] The preparation process of the PDMS-based coupling agent is as follows:

[0052] Dissolve 2 mmol triethoxysilyl butyraldehyde in 30 mL toluene, add 1 mmol NH2-PDMS-NH2, stir for 3-5 min, then drop 0.15 mL glacial acetic acid, heat to 120 °C and react for 24 h, then remove toluene by rotary evaporation to obtain a PDMS-based coupling agent.

[0053] NH2-PDMS-NH2 is amino-polydimethylsiloxane-amino with a molecular weight of 700.

[0054] Preparation Example 3

[0055] The preparation process of the wear-resistant component is as follows:

[0056] 10 g of the polystyrene-CeO2 composite microspheres prepared in Preparation Example 1 were ultrasonically dispersed in 120 mL of ethanol solution, 0.8 g of a PDMS-based coupling agent and 8 mL of a zinc chloride ethanol solution were added, wherein the mass fraction of zinc chloride in the zinc chloride ethanol solution was 11%, and the mixture was stirred and mixed at 70° C. for 12 h, and then filtered. The filter cake was washed with deionized water and dried to obtain a wear-resistant component.

[0057] The preparation process of the PDMS-based coupling agent is as follows:

[0058] Dissolve 2 mmol triethoxysilylbutyraldehyde in 30 mL toluene, add 1 mmol NH2-PDMS-NH2, stir for 4 min, then drop 0.4 mL glacial acetic acid, heat to 120 °C and react for 24 h, then remove toluene by rotary evaporation to obtain a PDMS-based coupling agent.

[0059] NH2-PDMS-NH2 is amino-polydimethylsiloxane-amino with a molecular weight of 3000.

[0060] Preparation Example 4

[0061] The preparation process of the wear-resistant component is as follows:

[0062] 10 g of the polystyrene-CeO2 composite microspheres prepared in Preparation Example 1 were ultrasonically dispersed in 150 mL of ethanol solution, 1 g of a PDMS-based coupling agent and 10 mL of a zinc chloride ethanol solution were added, wherein the mass fraction of zinc chloride in the zinc chloride ethanol solution was 12%, and the mixture was stirred and mixed at 80°C for 12 h, then filtered, and the filter cake was washed with deionized water and dried to obtain a wear-resistant component.

[0063] The preparation process of the PDMS-based coupling agent is as follows:

[0064] Dissolve 2 mmol triethoxysilylbutyraldehyde in 30 mL toluene, add 1 mmol NH2-PDMS-NH2, stir for 5 min, then drop 0.6 mL glacial acetic acid, heat to 120 °C and react for 24 h, then remove toluene by rotary evaporation to obtain a PDMS-based coupling agent.

[0065] NH2-PDMS-NH2 is amino-polydimethylsiloxane-amino with a molecular weight of 5000.

[0066] Preparation Example 5

[0067] The preparation of the wear-resistant component is different from that of Preparation Example 2, in that NH2-PDMS-NH2 is amino-polydimethylsiloxane-amino with a molecular weight of 1000.

[0068] Comparative Example 1

[0069] The preparation process of the wear-resistant component is as follows:

[0070] 10 g of the polystyrene-CeO2 composite microspheres of Preparation Example 1 were ultrasonically dispersed in 100 mL of ethanol solution, 0.5 g of PDMS-based coupling agent was added, and the mixture was stirred and mixed at 60°C for 12 h. The mixture was then filtered, and the filter cake was washed with deionized water and dried to obtain a wear-resistant component. The preparation process of the PDMS-based coupling agent was the same as that of Preparation Example 1.

[0071] Comparative Example 2

[0072] The preparation process of the wear-resistant component is as follows:

[0073] 10 g of the polystyrene-CeO2 composite microspheres prepared in Preparation Example 1 were ultrasonically dispersed in 100 mL of ethanol solution, 0.5 g of triethoxysilylbutyraldehyde and 5 mL of zinc chloride ethanol solution were added, the mass fraction of zinc chloride in the zinc chloride ethanol solution was 10%, and the mixture was stirred and mixed at 60°C for 12 h, then filtered, the filter cake was washed with deionized water and dried to obtain a wear-resistant component.

[0074] Example 1

[0075] A wear-resistant flexible polymer material comprises the following raw materials in parts by weight: 300 parts of random copolymer polypropylene, 250 parts of impact copolymer polypropylene, 210 parts of ethylene-octene copolymer, 45 parts of wear-resistant components of Preparation Example 2, 21 parts of antioxidant, 10 parts of nucleating agent, 9 parts of maleic anhydride grafted polypropylene, 4 parts of 3-amino-1,2,4-triazole, 14 parts of basic magnesium sulfate whisker, 13 parts of ultraviolet absorber and 7 parts of lubricant.

[0076] The antioxidant is antioxidant 1010 and antioxidant 168 in a mass ratio of 18:13. The preparation method of the above wear-resistant flexible polymer material comprises the following steps

[0077] Random copolymer polypropylene, impact copolymer polypropylene, maleic anhydride grafted product and aminotriazole are added to an internal mixer, and blended at a speed of 50 rpm and 100° C. for 15 minutes to obtain a pretreated material. The pretreated material, ethylene-octene copolymer, wear-resistant component, antioxidant, nucleating agent, ultraviolet absorber and lubricant are added to a twin-screw extruder through a main feeding port, and basic magnesium sulfate whiskers are added through a side feeding port, followed by melt extrusion. The screw temperature is 180-230° C. and the rotation speed is 200 rpm to obtain a wear-resistant flexible polymer material.

[0078] Example 2

[0079] A wear-resistant flexible polymer material comprises the following raw materials in parts by weight: 320 parts of random copolymer polypropylene, 270 parts of impact copolymer polypropylene, 220 parts of ethylene-octene copolymer, 50 parts of the wear-resistant component of Preparation Example 2, 30 parts of an antioxidant, 11 parts of a nucleating agent, 9 parts of maleic anhydride grafted polypropylene, 4 parts of 3,5-diamino-1,2,4-triazole, 14 parts of basic magnesium sulfate whiskers, 13 parts of an ultraviolet absorber, and 7 parts of a lubricant.

[0080] The antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 18:15

[0081] The preparation method of the above-mentioned wear-resistant flexible polymer material comprises the following steps:

[0082] Random copolymer polypropylene, impact copolymer polypropylene, maleic anhydride grafted product and aminotriazole are added to an internal mixer, and blended at a speed of 50 rpm and 100° C. for 15 minutes to obtain a pretreated material. The pretreated material, ethylene-octene copolymer, wear-resistant component, antioxidant, nucleating agent, ultraviolet absorber and lubricant are added to a twin-screw extruder through a main feeding port, and basic magnesium sulfate whiskers are added through a side feeding port, followed by melt extrusion, with a screw temperature of 190-220° C. and a rotation speed of 300 rpm to obtain a wear-resistant flexible polymer material.

[0083] Example 3

[0084] A wear-resistant flexible polymer material comprises the following raw materials in parts by weight: 350 parts of random copolymer polypropylene, 280 parts of impact copolymer polypropylene, 240 parts of ethylene-octene copolymer, 55 parts of the wear-resistant component of Preparation Example 2, 35 parts of an antioxidant, 12 parts of a nucleating agent, 10 parts of maleic anhydride grafted polypropylene, 5 parts of 5-amino-1H-1,2,4-triazole-3-carboxylic acid, 15 parts of basic magnesium sulfate whiskers, 15 parts of an ultraviolet absorber, and 8 parts of a lubricant.

[0085] The antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 20:15

[0086] The preparation method of the above-mentioned wear-resistant flexible polymer material comprises the following steps:

[0087] Random copolymer polypropylene, impact copolymer polypropylene, maleic anhydride grafted product and aminotriazole are added to an internal mixer, and blended at a speed of 50 rpm and 100° C. for 15 minutes to obtain a pretreated material. The pretreated material, ethylene-octene copolymer, wear-resistant component, antioxidant, nucleating agent, ultraviolet absorber and lubricant are added to a twin-screw extruder through a main feeding port, and basic magnesium sulfate whiskers are added through a side feeding port, followed by melt extrusion, with a screw temperature of 190-220° C. and a rotation speed of 300 rpm to obtain a wear-resistant flexible polymer material.

[0088] Example 4

[0089] A wear-resistant flexible polymer material, compared with Example 1, the difference is that the wear-resistant component is the product obtained in Preparation Example 3.

[0090] Example 5

[0091] A wear-resistant flexible polymer material, compared with Example 1, the difference is that the wear-resistant component is the product obtained in Preparation Example 4.

[0092] Example 6

[0093] A wear-resistant flexible polymer material, compared with Example 1, the difference is that the wear-resistant component is the product obtained in Preparation Example 5.

[0094] Example 7

[0095] A wear-resistant flexible polymer material, compared with embodiment 1, the difference lies in that the aminotriazole is 4-aminotriazole.

[0096] Example 8

[0097] A wear-resistant flexible polymer material, compared with Example 1, the difference is that the aminotriazole is 5-amino-1H-1,2,4-triazole-3-carboxylic acid ethyl ester.

[0098] A wear-resistant flexible polymer material, compared with Example 1, the difference is that the wear-resistant component is the product obtained in Preparation Example 1.

[0099] Comparative Example 2

[0100] A wear-resistant flexible polymer material, compared with Example 1, the difference is that the wear-resistant component is the product obtained in Control Example 1.

[0101] Comparative Example 3

[0102] A wear-resistant flexible polymer material, compared with Example 1, the difference is that the wear-resistant component is the product obtained in Control Example 2.

[0103] Comparative Example 4

[0104] A wear-resistant flexible polymer material, compared with embodiment 1, the difference is that the preparation method of the wear-resistant flexible polymer material comprises the following steps

[0105] Random copolymer polypropylene, impact copolymer polypropylene, maleic anhydride grafted product, aminotriazole, ethylene-octene copolymer, wear-resistant component, antioxidant, nucleating agent, ultraviolet absorber and lubricant are added into a twin-screw extruder through a main feeding port, and basic magnesium sulfate whisker is added through a side feeding port, followed by melt extrusion. The screw temperature is 180-230°C and the rotation speed is 200rpm to obtain a wear-resistant flexible polymer material.

[0106] The wear-resistant flexible polymer materials obtained in Examples 1 to 8 and Comparative Examples 1 to 4 were subjected to performance tests, and the test process was as follows:

[0107] Mechanical properties: Each group of wear-resistant flexible polymer materials was injection molded to prepare test standard specimens. The tensile properties of the materials were tested according to GB / T1040.2-2018. The specimens were 1A type specimens, the tensile rate was 50mm / min, and the gauge length was 50mm. A JJ-5.5J cantilever beam impact testing machine was used, the test standard was GB183-80, the sample was a V-notch with an angle of 45°, and the impact performance was tested.

[0108] Wear resistance: The mass wear test standard is GB / T 5478-2008, mass wear (H18, 9.8N, 1000r), unit: g / (1000r).

[0109] The results are shown in Table 1:

[0110] Table 1

[0111]

[0112]

[0113] According to the data recorded in Table 1, the wear-resistant flexible polymer material prepared by the present invention has a tensile strength of 34.1-35.2 Mpa and an impact strength of 52.4-55.2 J / cm at 25°C. 2 , -30℃ impact strength is 15.5-16.3J / cm 2 , abrasion is 0.007-0.011g / (1000r), and it has good mechanical properties and wear resistance. Specifically, it can be seen from the test results of Example 1 and Comparative Example 1 that without coupling treatment of polystyrene-CeO2 composite microspheres, the mechanical properties and wear resistance of the wear-resistant flexible polymer material are significantly reduced. It can be seen from the test results of Example 1 and Comparative Example 2 and Comparative Example 3 that the use of conventional silane coupling agent treatment or the omission of the addition of zinc chloride will cause the wear resistance or mechanical properties of the wear-resistant flexible polymer material to deteriorate to varying degrees. It can be seen from the test results of Example 1 and Comparative Example 4 that it is preferentially allowed to react random copolymer polypropylene, impact copolymer polypropylene, maleic anhydride grafted product and aminotriazole at 100°C for a period of time, which is beneficial to improving the strength and toughness of the material.

[0114] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0115] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A wear-resistant flexible polymer material, characterized in that: The invention comprises the following raw materials in parts by weight: 300-350 parts of random copolymer polypropylene, 250-280 parts of impact copolymer polypropylene, 210-240 parts of ethylene-octene copolymer, 45-55 parts of wear-resistant component, 21-35 parts of antioxidant, 10-12 parts of nucleating agent, 9-10 parts of maleic anhydride graft, 4-5 parts of aminotriazole, 14-15 parts of basic magnesium sulfate whisker, 13-15 parts of ultraviolet absorber and 7-8 parts of lubricant; The wear-resistant component is a PDMS-based coupling agent modified polystyrene-CeO2 composite microsphere.

2. A wear-resistant flexible polymer material according to claim 1, characterized in that: The preparation process of the wear-resistant component is as follows: The polystyrene-CeO2 composite microspheres are ultrasonically dispersed in an ethanol solution, a PDMS-based coupling agent and a zinc chloride ethanol solution are added, the mixture is stirred and mixed at 60-80°C for 12 hours, the mixture is filtered, the filter cake is washed and dried, and the wear-resistant component is obtained.

3. A wear-resistant flexible polymer material according to claim 2, characterized in that: The dosage ratio of the polystyrene-CeO2 composite microspheres, the ethanol solution, the PDMS-based coupling agent and the zinc chloride ethanol solution is 10g: 100-150mL: 0.5-1g: 5-10mL, and the mass fraction of zinc chloride in the zinc chloride ethanol solution is 10-12%.

4. A wear-resistant flexible polymer material according to claim 2, characterized in that: The preparation process of the PDMS-based coupling agent is as follows: Dissolve triethoxysilylbutyraldehyde in toluene, add NH2-PDMS-NH2, stir for 3-5 minutes, then drop glacial acetic acid, heat to 120°C and react for 24 hours, remove toluene by rotary evaporation to obtain a PDMS-based coupling agent.

5. A wear-resistant flexible polymer material according to claim 4, characterized in that: The usage ratio of triethoxysilylbutyraldehyde, toluene, NH2-PDMS-NH2 and glacial acetic acid is 2mmol:30mL:1mmol:0.15-0.6mL.

6. The wear-resistant flexible polymer material according to claim 4, characterized in that: NH2-PDMS-NH2 is amino-polydimethylsiloxane-amino with a molecular weight of 700-5000.

7. The wear-resistant flexible polymer material according to claim 2, characterized in that: The preparation process of the polystyrene-CeO2 composite microspheres is as follows: Step a, adding distilled water, styrene, divinylbenzene and methacrylic acid into a reaction kettle, stirring evenly under nitrogen protection, heating to 75° C., adding potassium persulfate solution, keeping the temperature for reaction for 6 hours, and cooling to room temperature to obtain a polystyrene microsphere emulsion; Step b, adding the polystyrene microsphere emulsion into distilled water, adding hexamethylenetetramine and cerium nitrate hexahydrate after ultrasonic dispersion for 10 minutes, reacting at 75° C. for 2 hours under stirring conditions, then centrifuging, washing the precipitate with anhydrous ethanol and drying to obtain polystyrene-CeO2 composite microspheres.

8. The wear-resistant flexible polymer material according to claim 1, characterized in that: The aminotriazole is at least one of 3-amino-1,2,4-triazole, 3,5-diamino-1,2,4-triazole, 5-amino-1H-1,2,4-triazole-3-carboxylic acid, 4-aminotriazole, 5-amino-1H-1,2,4-triazole-3-ethylcarboxylate and 5-amino-1H-1,2,4-triazole-3-carboxylic acid.

9. A method for preparing a wear-resistant flexible polymer material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Random copolymer polypropylene, impact copolymer polypropylene, maleic anhydride grafted product and aminotriazole are added to an internal mixer, and blended at a speed of 50 rpm and 100° C. for 15 minutes to obtain a pretreated material. The pretreated material, ethylene-octene copolymer, wear-resistant component, antioxidant, nucleating agent, ultraviolet absorber and lubricant are added to a twin-screw extruder through a main feeding port, and basic magnesium sulfate whiskers are added through a side feeding port, followed by melt extrusion to obtain a wear-resistant and flexible polymer material.

10. The wear-resistant flexible polymer material according to claim 9, characterized in that: The screw temperature of the twin-screw extruder is 180-230° C., and the rotation speed is 200-600 rpm.